Modular isoquinoline synthesis using catalytic enolate arylation and in situ functionalization. - Pilgrim, B; Gatland, A; McTernan, C; Procopiou, P; Donohoe, T (2013)
A methyl ketone, an aryl bromide, an electrophile, and ammonium chloride were combined in a four-component, three-step, and one-pot coupling procedure to furnish substituted isoquinolines in overall yields of up to 80%. This protocol utilizes the palladium catalyzed α-arylation reaction of an enolate, followed by in situ trapping with an electrophile, and aromatization with ammonium chloride. tert-Butyl cyanoacetate participated in a similar protocol; after functionalization and decarboxylation, 3-amino-4-alkyl isoquinolines were prepared in high yield.